2008
DOI: 10.1002/pbc.21050
|View full text |Cite
|
Sign up to set email alerts
|

Acute myelogenous leukemia associated with Ollier disease

Abstract: Ollier disease is a rare disorder characterized by the presence of multiple enchondromas and a propensity to develop malignancies. We report the case of a 7-year-old Caucasian male with Ollier disease who developed acute myelogenous leukemia (AML). This report describes a patient with Ollier disease and AML and may offer a clue into the genetic pathogenesis of these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Patients with Ollier disease and Maffucci syndrome have a significant risk of developing a second unrelated cancer 17, the most common of which is glioma 23–33. Although less common, there are also reports of patients with Ollier disease who develop acute myeloid leukaemia (AML) 34–36. It is also of interest that an IDH1 R132C mutation has recently been detected at the Wellcome Trust Sanger Institute in the HT1080 cell line, described originally as deriving from a fibrosarcoma of bone 37.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with Ollier disease and Maffucci syndrome have a significant risk of developing a second unrelated cancer 17, the most common of which is glioma 23–33. Although less common, there are also reports of patients with Ollier disease who develop acute myeloid leukaemia (AML) 34–36. It is also of interest that an IDH1 R132C mutation has recently been detected at the Wellcome Trust Sanger Institute in the HT1080 cell line, described originally as deriving from a fibrosarcoma of bone 37.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular diseases are the main cause of death in the world; the majority of fatal events are myocardial infarctions (MI) and the resulting heart failure [1]. Acute myocardial infarction is due to a myocardial necrotic event caused by an unstable ischemic syndrome [2], with blockage or occlusion of the coronary artery [3]. As a consequence of this dramatic event, a portion of myocardial tissue undergoes a process of adverse changes that consist of left ventricular (LV) remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple enchondromatosis is a rare heterogeneous skeletal disease, which can be divided into six subtypes as follows: Ollier disease, Maffucci syndrome, metaphyseal chondromatosis, metatarsal chondromatosis, spinal interstitial chondrodysplasia and spinal interstitial chondromatosis (6). Over the years, it has been reported that Ollier disease may be associated with pelvic diseases, hematological diseases, gliomas of the skull base, pancreatic cancer and other diseases (7)(8)(9)(10)(11)(12)(13)(14), and this has guided clinicians in the diagnosis of patients who may have Ollier disease. However, attention should be paid to lesions of the nervous system (15), digestive system (16) and blood system.…”
Section: Discussionmentioning
confidence: 99%